tìm x, y biết \(x+y+12=4\sqrt{x}-6\sqrt{y-1}\)
Tìm x , y biết :
\(x+y+12=4\sqrt{x}+6\sqrt{y-1}\)
Giả sử \(x^3\ge y^2\)và \(x,y\in Q^+\)
Tìm x,y để \(\sqrt{\frac{x-8.\sqrt[6]{x^3y^2}+4.\sqrt[3]{y^2}}{\sqrt{x}-2.\sqrt[3]{y}+2.\sqrt[12]{x^3.y^2}}+3.\sqrt[3]{y}}+\sqrt[6]{y}=1\)
Tìm x, y biết: \(x+y+12=4\sqrt{x}+6\sqrt{y-1}\)
Phương pháp 5. Biến đổi về dạng tổng các bình phương \(A^2+B^2+C^2=0\)
a \(x+y+12=4\sqrt{x}+6\sqrt{y-1}\)
b \(x+y+z+35=2\left(2\sqrt{x+1}+3\sqrt{y+2}+4\sqrt{z+3}\right)\)
c \(9x+17=6\sqrt{8x+1}+4\sqrt{x+3}\)
d \(\sqrt{x}+2\sqrt{x+3}=x+4\)
e\(\sqrt{3-x}+2\sqrt{3x-2}-3=x\)
\(\left(5\right)\sqrt{x+3-4\sqrt{x-1}}\sqrt{x+8+6\sqrt{x-1}}=5\)
\(\left(6\right)2x^2+3x+\sqrt{2x^2+3x+9}=33\)
\(\left(7\right)\sqrt{3x^2+6x+12}+\sqrt{5x^4-10x^2+30}=8\)
\(\left(8\right)x+y+z+8=2\sqrt{x-1}+4\sqrt{y-2}+6\sqrt{z-3}\)
Giaỉ phương trình:
1, x + y + 12= 4\(\sqrt{x}+6\sqrt{y-1}\)
2, \(x+y+z=2\sqrt{x-1}+2\sqrt{y-5}+2\sqrt{z+3}\)
3, \(\sqrt{3x^2+12x+13}+\sqrt{4x^2+16x+25}=-x^2-4x\\\)
4, \(\sqrt{x+3-4\sqrt{x-1}}+\sqrt{x+8+6\sqrt{x-1}}=5\)
Tim x,y biet ;\(x+y+12=4\sqrt{x}+6\sqrt{y-1}\)
\(x+y+12=4\sqrt{x}+6\sqrt{y-1}\)